Combination therapy with GLP‐1 receptor agonist and SGLT2 inhibitor - DeFronzo, Ralph A. (Diabetes, obesity & metabolism, 2017)
The SGLT2 inhibitors (SGLTi) and glucagon‐like‐1 receptor agonists (GLP‐1 RAs) effectively reduce HbA1c, but via very different mechanisms, making them an effective duet for combination therapy. Recently, drugs in both of these antidiabetic classes have been shown to reduce cardiovascular events, most probably by different mechanisms. SGLT2i appear to exert their CV protective actions by haemodynamic effects, while GLP‐1 RAs work via anti‐atherogenic/anti‐inflammatory mechanisms, raising the possibility that combined therapy with these 2 classes may produce additive CV benefits. The SGLT2i and GLP‐1 RAs also reduced macroalbuminuria, decreased the time for doubling of serum creatinine, and slowed the time to end‐stage renal disease. In this perspective, we review the potential benefit of combination SGLT2i/GLP‐1 RA therapy on metabolic‐cardiovascular‐renal disease in patients with type 2 diabetes mellitus.